Professional Networks, Innovative Motivation, and Learning Innovation Among Islamic Religious Education Teachers at Schools in Indonesia: An Analysis of SEM-PLS - M. Mujab; Nur Ali; Angga Dwi Mulyanto; Anis Malik Thoha; Benny Afwadzi; Mahbub Humaidi Aziz (Progresiva : Jurnal Pemikiran dan Pendidikan Islam, 2025)
The purpose of this study is to explore the influence of professional networks and innovative motivation on learning innovation, especially in Islamic Religious Education (IRE/PAI, Pendidikan Agama Islam) teachers at schools in Indonesia. This study uses a quantitative approach with Structural Equation Modeling - Partial Least Squares (SEM-PLS) analysis. There were 241 IRE teacher respondents from various schools in Indonesia who participated in this study. The results of this analysis confirm that professional network significantly positively influences innovative motivation and learning innovation. Similarly, innovative motivation has a significant effect on learning innovation. Innovative motivation also significantly mediates the effect of social network on learning innovation. These findings mean that if professional networks are strong and innovative motivation is also great, learning innovation will increase. This research is limited to IRE teachers in Indonesia. This research adds value by focusing on the importance of professional networks and innovative motivation in encouraging increased learning innovation. It also provides new insights to education policy makers and school administrators on strategies to increase teachers' involvement in professional networks. In addition, encouraging teachers' motivation to innovate is also very important to improve their learning innovation.